Hydroxychloroquine in systemic lupus erythematosus, anti-SSA/SSB, and antiphospholipid antibody-positive pregnancies - Saleh, Zeinab F.; Somers, Emily C.; Romero, Vivian C.; Marder, Wendy (American journal of obstetrics and gynecology, 2025)
Pregnancies in patients with systemic lupus erythematosus (SLE) and those positive for anti-SSA/SSB or antiphospholipid antibodies carry a heightened risk of adverse pregnancy outcomes (APOs), including preeclampsia, preterm birth, and congenital heart block. Among available therapies, hydroxychloroquine (HCQ) plays a pivotal role due to its immunomodulatory and antithrombotic properties, which may help improve pregnancy outcomes. Emerging evidence supports HCQ's role in reducing SLE flares, as well as lowering the recurrence risk of congenital heart block in anti-SSA/SSB–positive pregnancies. Additionally, in patients with antiphospholipid antibodies, HCQ may serve as an adjunctive therapy to mitigate obstetric complications, particularly in refractory cases. Despite early concerns about teratogenicity, large cohort studies and international guidelines affirm HCQ's safety at standard doses (≤400 mg/day), with no consistent association with congenital malformations (CMs). Recent research suggests that subtherapeutic HCQ blood levels during pregnancy may correlate with higher maternal disease activity and adverse pregnancy outcomes, though their primary utility currently lies in identifying nonadherence. Given the heightened risk of pregnancy complications in this population, a clear understanding of HCQ's essential role is crucial for both patients and their multidisciplinary care teams. This review provides up-to-date information on HCQ in pregnancy to help guide clinical decision-making. [Display omitted]